Butachlor Tolerance in Wheat Seedlings - Singh, Hemlata; Dolui, Subhrojit; Kumar, Rajeev; Pal, S.; Bhattacharya, A. (International Journal of Economic Plants, 2022)
Butachlor, though reported to adversely affect growth by interfering with amino acid and protein synthesis, is still recommended for weed control in wheat. The present study reports for the first time the butachlor dose-dependent activation of phenol metabolism in wheat. Application of herbicide leads to stress in plant and it is well known fact that plants growing under stressful condition biosynthesize more phenolic compounds in comparison to plants growing under normal conditions. All the butachlor treatments stimulated the mean guaiacol peroxidase (GPX) activity while all but one (double the recommended field dose, 2RFD) of the treatments enhanced phenylalanine ammonia lyase (PAL) activity. The mean phenol content, which is dependent on relative activities of PAL and GPX, increased significantly at the lowest application rate (half the recommended field dose, 0.5RFD) of butachlor. The mean PAL activity and mean phenol content increased significantly on 20 and 30 days after application while mean GPX activity declined progressively throughout the experimental period. Butachlor-induced PAL activity showed hyperbolic dependence on its substrate, phenylalanine concentration that conformed Michaelis-Menten kinetics. Measurement of kinetic parameters of PAL indicated that the maximum velocity (Vmax) remains unchanged (11.1 µmolt-cinnamic acid produced h-1 g-1) while Michaelis constant (Km) varied between 2.24 and 5.34 µM and increased with increasing butachlor treatments. Butachlor at its lower application rate with its role as a positive modulator of PAL enhances phenol accumulation, which forms a part of butachlor tolerance in wheat.